Universality of Brunnian (N-body Borromean) four- and five-body systems - Yamashita, Marcelo Takeshi [UNESP]; Fedorov, D. V.; Jensen, A. S. (Amer Physical Soc, 2010)
We compute binding energies and root-mean-square radii for weakly bound systems of N = 4 and 5 identical bosons. Ground and first excited states of an N-body system appear below the threshold for binding the system with N - 1 particles. Their root-mean-square radii approach constants in the limit of weak binding. Their probability distributions are on average located in nonclassical regions of space which result in universal structures. Radii decrease with increasing particle number. The ground states for more than five particles are probably nonuniversal, whereas excited states may be universal.